Biofilm formation on RO membranes: the impact of seawater pretreatment - Ben-Dov, Eitan (2016)
Membrane biofouling is an acute problem that interferes with filtration and pressure-driven desalination processes. In this study, ultrafiltration (UF) and membrane bioreactor (MBR) system were examined for their potential use in the removal of organic matter from seawater as pretreatment for reverse osmosis (RO) desalination. The study showed that MBR treatment equipped with UF decreases total organic carbon, polysaccharides, and biofouling potential of RO membrane in comparison to feed seawater after UF treatment alone. Bacteria in the feed water and in the MBR system were characterized. The most abundant heterotrophic bacteria nourished from organic substances present in the MBR system belonging to the Alphaproteobacteria and Gammaproteobacteria classes increased from ~40% in seawater to ~60% in the MBR. These results indicate that pretreatment using a seawater MBR system can improve RO feed water quality and reduce the biofouling potential of RO membranes.